Validation of a numerical simulation of the North Atlantic Ocean with ARGO Data - Gómez Navarro, Laura (2014)
The outputs of a numerical simulation have been validated with Argo data; with the idea of being able to use these outputs to assimilate SSS information retrieved by the satellite SMOS. In addition to Argo data, the model is also compared against the WOA09 climatology. There are a considerable amount of valid profiles available during year 2012, and the coverage does not have temporal biases, as the amount of data is homogeneous throughout the year. This demonstrates that choosing Argo to validate the simulation was a correct choice. The results show that there exists a reasonable agreement between model and Argo data in the open Ocean. However, it has been observed that the simulation still contains spatial and temporal errors probably due to a bad representation of certain oceanic processes. Nevertheless, as the errors are easily identified and do not cover the open Ocean in the tropical and subtropical regions, the simulation could still be considered as an appropriate tool to improve the remote sensing of SSS data.